AN EVALUATION OF THE PROFESSIONAL COMPETENCE OF THE NIGERIA CERTIFICATE IN EDUCATION (NCE) TEACHERS OF NATIONAL TEACHERS’ INSTITUTE DISTANCE LEARNING PROGRAMME (2011)
The National Teachers’ Institute (NTI) has been involved in training teachers for the Nigeria Certificate in Education (NCE) for over three decades through Distance Learning Programme. The quality of these teachers has been queried particularly when compared with those who undertake full-time NCE Programme. However, this claim has not been verified empirically. This study, therefore, evaluated the professional competencies of NCE teachers produced by the NTI Distance Learning Programme. The study further examined the extent to which NTI primary school teachers’ gender, years of teaching experience, morale, motivation, attitude, expectation from the teaching milieu, commitment, values development, length of training accounted for their professional competencies. Five research questions were answered. The study adopted a causal comparative design. Forty NCE teachers produced by NTI Distance Learning Programme and 40 Full-time NCE trained teachers were purposively selected from schools in eight local government areas of Ogun State. Six instruments were used for data collection. These are Classroom Interaction Sheet (r =0.85), Instructional Competence Rating Scale (r =0.68), Teachers’ Knowledge of Social Studies Content (r =0.72), Teacher Morale Scale (r =0.75), Motivation to work Scale (r =0.82) and Teachers’ Characteristic Questionnaire (r =0.88). Data were analysed using descriptive, t-test and multiple regression statistics. There was no significant difference in the professional competence of NTI NCE teachers and Full-time NCE teachers on knowledge of subject matter. Generally on the average, the NTI NCE teachers used 71% of the instructional time in facilitating learning but pupils were not actively involved in the teaching learning process. The NTI NCE teachers were significantly committed to teaching more than the full-time teachers (t (78) = 2.02, p<0.05). Gender, years of teaching experience, attitude to teaching, expectation from the teaching milieu, values development, motivation to work and teachers’ morale did not significantly influence professional competence. All the factors jointly contributed a multiple R of 0.294, R² of 0.086 and adjusted R² of 0.183 accounted for 18.3% of the variance in the teachers’ professional competence. The NTI NCE teachers were found to be more committed to teaching than the Full-time NCE teachers. However, mode of study did not influence professional competence of NCE teachers. In view of the fact that teachers will continue to access professional training by NTI, there is, therefore, the need for NTI to ensure a favourable teaching environment in order to enhance the production of committed teachers. Therefore, the NTI Programme should be sustained because of its role in the training of teachers